(untitled) (UNED Research Journal, 2019)
The state of Veracruz, Mexico, has suffered frequent flooding in recent years linked to climate change. The aim of this study was to identify the vulnerability and social resilience in school youth at three locations: Cotaxtla, Tlacotalpan y José Cardel. A survey was applied to 411 students and interviews were carried out with 16 key stakeholders. The findings of this consultation process indicated a lack of knowledge in the actions to manage their vulnerability and the regional impacts aggravated by climate change, which was used as an input to design environmental education workshops on the vulnerability and social resilience to climate change. A total of 436 students and 42 teachers participated in the workshops, with involvement from government agencies. This process achieved a greater sensibilization of the students and teachers to the regional impacts of climate change, mitigation and adaptation actions, inter and intracommunity networks were developed and risk maps were created. The work carried out is the beginning in a series of environmental education tasks that need to be developed, with the aim that the communities, through their social learning, can strengthen and energize their social resilience in the face of the risks of climate change.